SISTEM PAKAR MENDIAGNOSA PENYAKIT CAMPAK DAN RUBELLA DENGAN METODE FORWARD CHAINING BERBASIS WEB - Asep Herman; Fungki Darmawan (UNIVERSITAS KEBANGSAAN, 2020)
Abstract:The development of technology is growing rapidly, one of which is to facilitate human activities by continuing to create new things such as Artificial Intelligence (AI) Systems that can help solve problems easily from the help of computers. The problem that will be discussed in this study is